Investigation on strength of reinforced clayey sand - Chegenizadeh, Amin; Nikraz, Hamid (Institute of Electrical and Electronics Engineers, Inc., 2011)
Composite soils have been widely used in civil engineering applications, especially in slopes, embankment dam and landfills. This paper aims to investigate effect of fiber inclusion on Unconfined Compressive Strength of composite soil (i.e. sand composite). Clayey sand was selected as soil part of the composite and plastic fiber was used as reinforcement. A series of laboratory Unconfined Compression tests carried out to evaluate fiber effect on strength behavior of composite sand. As the test program involved so many degree of freedom in terms of parameter. Test program was designed carefully. While the soil material kept constant, the fiber parameters differed from one test to another. Fiber lengths were changed from 10 mm to 30 mm and fiber content were selected as 0.1% and 0.3%. For each test, stress_strain graph derived and the results were compared. The results proved that inclusion of fiber affected strength behavior of sand composite so that increasing in fiber content and length caused increasing in Unconfined Compressive Strength (UCS).